Energy‐dense fast food products cost less: an observational study of the energy density and energy cost of Australian fast foods - Lyndal Wellard; Michelle Havill; Clare Hughes; Wendy L. Watson; Kathy Chapman (Elsevier, 2015)
Abstract Objective: To examine the association between energy cost and energy density of fast food products. Methods: Twenty Sydney outlets of the five largest fast food chains were surveyed four times. Price and kilojoule data were collected for all limited‐time‐only menu items (n=54) and a sample of standard items (n=67). Energy cost ($/kilojoule) and energy density (kilojoules/gram) of menu items were calculated. Results: There was a significant inverse relationship between menu item energy density and energy cost (p<0.001). Salads had the highest energy cost, while value items, meals that included a dessert and family meals had the lowest. Conclusions: Fast food chains could provide a wider range of affordable, lower‐energy foods, use proportional pricing of larger serve sizes, or change defaults in meals to healthier options. More research is required to determine the most effective strategy to reduce the negative impact of fast food on the population's diet. Implications: Current pricing in the fast food environment may encourage unhealthier purchases.